Early Outcome of Conventional Coronary Artery Bypass Grafting with Peri-operative Hyperglycaemia in Diabetic and Non- Diabetic Patients in NICVD, Dhaka - Ahsan, Syed Imtiaz; Sabur, SMA (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Peri-operative hyper glycaemia has been defined as the average of blood glucose test obtained by venous or arterial sampling on the day of and the day after surgery. Here the association between peri-operative hyper glycaemia and outcomes among patients undergoing coronary artery bypass grafting was measured. Objectives: Evaluation of early outcome of conventional coronary artery bypass grafting with perioperative hyperglycemia in diabetic and non-diabetic patients & to compare the outcomes in both the groups. Methodology: The study was a prospective observational analytic study conducted in National Institute of Cardiovascular Diseases, Dhaka from January 2010 to December 2011 in 60 patients having ischaemic heart disease with or without diabetes mellitus. Result: Postoperative ventilation time and ICU stay both were significantly longer in the diabetic group as compared to their non-diabetic counterparts (p<0.001). Pneumonia and all other infections and complications were also more in the former group. None in either group died. The diabetic group stayed on an average 4 days more than the non-diabetic group (p<0.001). Conclusion: The study concluded that outcome of coronary revascularization in non-diabetic patients with peri-operative hyper glycaemia is better than that in diabetic patients with peri operative hyper glycaemia. J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 39-42